Optimizing MSME Branding Through Artificial Intelligence (AI) Technology to Increase Competitiveness in the Digital Market - Moh. Badri Tamam; Rahmawati Ardila (Turast: Jurnal Penelitian dan Pengabdian, 2025)
Design interacts with many disciplines and plays an important role in marketing by attracting the attention of the target market, which influences their purchasing decisions. A brand is more than just a name, logo, or symbol; it encompasses everything that is in the minds of consumers. A logo, as the face of a brand, helps customers recognize products and associate them with certain associations, so it must represent the entity uniquely. Artificial intelligence (AI) technology has become a very useful tool in branding in today's digital age. AI enables MSMEs to create and optimize branding strategies more easily and effectively by analyzing market trends, understanding consumer preferences, and creating designs that are attractive and relevant to the target market. In addition, AI helps automate time-consuming marketing tasks, allowing MSMEs to focus on developing their products and services. This training aims to provide MSME players with insights and skills in applying AI technology for branding needs. With this training, it is hoped that MSME players will be able to increase the competitiveness of their products in an increasingly competitive market and create a strong and sustainable brand. Based on the workshop results, 66% of participants understood well and 18% understood the role of product branding as an identity recognized by consumers. Overall, this workshop succeeded in providing an important foundation for MSME players to develop creativity and innovation in their product branding, which was previously still simple.